2016
DOI: 10.5395/rde.2016.41.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiant exposure and wavelength spectrum of light-curing units on chemical and physical properties of resin cements

Abstract: ObjectivesIn this study, we evaluated the influence of different radiant exposures provided by single-peak and polywave light-curing units (LCUs) on the degree of conversion (DC) and the mechanical properties of resin cements.Materials and MethodsSix experimental groups were established for each cement (RelyX ARC, 3M ESPE; LuxaCore Dual, Ivoclar Vivadent; Variolink, DMG), according to the different radiant exposures (5, 10, and 20 J/cm2) and two LCUs (single-peak and polywave). The specimens were made (7 mm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Thus, they conclude that only third-generation LCUs were suitable for different types of photoinitiators, and improved properties of resin materials [25]. A study comparing different resin cements with radiant exposures (5, 10, and 20 J/cm 2 ) using single and polywave LCU showed that the modulus of elasticity was higher for radiant exposures of 10 and 20 J/cm 2 [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they conclude that only third-generation LCUs were suitable for different types of photoinitiators, and improved properties of resin materials [25]. A study comparing different resin cements with radiant exposures (5, 10, and 20 J/cm 2 ) using single and polywave LCU showed that the modulus of elasticity was higher for radiant exposures of 10 and 20 J/cm 2 [12].…”
Section: Discussionmentioning
confidence: 99%
“…This limits its use in bleaching teeth [9,10]. Certain new photoinitiators are activated at different wavelengths [11], such as phenilpropanodione (PPD, 393 nm), bisacrylphosphine oxide (BAPO, 370 nm), and monoacrylphosphine (MAPO, 380 nm) [12]. Polywave LED devices are necessary to activate these new photoinitiators because these emit a spectrum of light varying between 385 and 515 nm, which can correspond to a maximum power of 3500 mW/cm 2 [11].…”
Section: Introductionmentioning
confidence: 99%
“…37 Kamferokinon dıĢındaki diğer fotoaktivatörler, 410 µm dalga boyundaki ıĢığa daha hassas ve 450-480 µm dalga boyu arasındaki ıĢığa ise daha az hassas mono asilfosfin oksit (Lucirin TPO) veya 1-Fenil 1,2-Propandiyon (PPD) dur. 38,39 Bu nedenle birinci ve ikinci nesil LED ıĢık kaynakları, yapılarında kamferokinon dıĢındaki reaksiyon baĢlatıcıları içeren kompozit rezinler üzerine etkili olmayabilmektedir. Etkili polimerizasyon sağlamak amacıyla LED ıĢık kaynakları kullanılacağı zaman, polimerize edilecek restoratif materyalin yapısı iyi bilinmelidir.…”
Section: Birinci Nesil Led ıģıK Cihazlarıunclassified
“…Restoration size and tooth properties, including the quality and thickness of the remaining dentin, also affect intrapulpal temperatures [17]. About 40 years, halogen lamp technology that had been adapted from the airplane industry was the main light source used for curing dental resin composites [18,19] But in the last decade, LCUs using Light Emitting Diode (LED) technology have replaced Quartz-Tungsten-Halogen (QTH) devices [20]. LED has many distinct advantages: requires a low power, can be easily battery powered, no filament or optical filter, has a long lifetime source, and provides much greater photon-generating efficiency than any competitive light source [19].…”
Section: Introductionmentioning
confidence: 99%